Effects of dual-task interference on dexterity performance in people with mild to moderately severe Parkinson's disease: An observational analysis. - Proud, Elizabeth; Morris, Meg E.; Bilney, Belinda; Miller, Kimberly J.; Nijkrake, Maarten J.; Munneke, Marten M.; McGinley, Jennifer L. (Journal of Hand Therapy, 2025)
Debilitating problems with hand function experienced by people with Parkinson's disease (PD) can worsen during multitasking. To investigate the effects of dual-task interference on a pegboard task in people with mild to moderately severe PD. Descriptive analysis. A secondary analysis of baseline data from the ParkinsonNet physiotherapy study conducted in 2006 in the Netherlands. The 9-hole peg test was performed with the more affected hand under single- and dual-task conditions. In dual-task trials, a cognitive task was added. The patient specific index-Parkinson's disease identified two functional priority groups—those reporting arm and hand problems as a priority for allied health management ("upper extremity priority") and those prioritizing other issues ("other priority"). We investigated differences in single- and dual-task performance at different levels of disease severity (Hoehn and Yahr stage) and for the two priority groups, and calculated the dual-task effect. Participants were 566 people with PD (Hoehn and Yahr stages I-IV). Dual-task interference occurred at each disease stage. Significant interactions existed between the task condition and disease severity (F (3, 559) = 4.28, p = 0.005) and task condition and priority group (F (1, 561) = 4.44, p = 0.036). Dual-task interference was greater in participants with more advanced disease or those prioritizing upper extremity problems. We described the effects of dual-task interference on more affected hand performance of a standardized dexterity test in a broad sample of people with PD. Dual-task interference may impact the daily lives of people with PD, especially those with more severe disease or who report arm and hand problems. It is important for clinicians to consider dual-task interference during upper extremity assessment and treatment. • Dual-task interference affects dexterity in all stages of Parkinson's disease. • Effects on performance are greater in those with more advanced diseases. • Dual tasking is a consideration for upper extremity assessment and treatment.